Gamma-glutamyltransferase as a preoperative differential diagnostic marker in patients with adnexal mass. (August 2019) - Reiser, Elisabeth; Aust, Stefanie; Seebacher, Veronika; Reinthaller, Alexander; von Mersi, Hannah; Schwameis, Richard; Polterauer, Stephan; Grimm, Christoph; Helmy-Bader, Samir
Abstract: Objective: Gamma-glutamyltransferase (GGT) is involved in tumor development, progression and chemotherapy resistance. The present study evaluated GGT serum levels as a preoperative predictive marker for ovarian cancer in patients with adnexal mass. Study design: Preoperative GGT serum levels of 2235 patients with adnexal mass and subsequent surgery were ascertained (patients with benign ovarian tumors: n = 1811; borderline tumor of the ovary [BTO]: n = 85; epithelial ovarian cancer [EOC]: n = 339). Standardized expert transvaginal ultrasound was documented. Results: Median (interquartile range) GGT serum levels in patients with benign ovarian tumors, BTO, and EOC were 15.0 U/l (11.0–23.0), 17.0 U/l (10.0–23.5), and 20.0 U/l (13.0–34.0), respectively (p = 0.002). Elevated GGT serum levels were associated with the presence of BTO/EOC in univariate analysis (p < 0.0001, hazard ratio 1.8, confidence interval 1.5–2.3). GGT did not outperform established tools for preoperative prediction of BTO/EOC in patients with adnexal mass, such as CA-125 measurement or transvaginal ultrasound. Conclusion: Elevated GGT serum levels were not associated with the presence of BTO/EOC in women with suspicious adnexal mass in multivariate analysis. GGT serum levels did not outperform established risk factors and therefore might add only limited additional value to CA-125 serum levels in the differential diagnosis between benign and malignant adnexal masses.